Design and performance evaluation of a coded aperture imaging system for real-time prompt gamma-ray monitoring during proton therapy. (September 2020) - Sun, Shifeng; Liu, Yang; Ouyang, Xiaoping
Abstract: A new mechanical collimated system capable of 2-dimensional (2D) prompt gamma-ray imaging is proposed for proton beam range verification and dose monitoring. To achieve high detection efficiency and high spatial resolution, a 2D thick mask with 50% open area and a novel near-field coded aperture imaging model were used. The performances of the system were evaluated for an imaginary line source and for proton beams incident on a cylindrical PMMA phantom by Geant4 Monte Carlo simulations. With a system-to-source distance of 230 mm, the system detection efficiency was 1.28 × 10 −4 events per incident 122.7 MeV proton. High quality 2D images of prompt gamma-ray emission for therapeutic proton beams can be reconstructed from the detector measurements. For 10 10 incident protons, the system was able to estimate the beam range with an error of less than 0.8 mm, without the need to align the system with the Bragg peak. Simulation results indicated that the system has the potential for accurate and real-time monitoring of proton therapy. Highlights: Novel system design for 2D prompt gamma-ray imaging during proton therapy was proposed. A 2D thick aperture with 50% open fraction which provides high detection efficiency was used. High quality 2D images of PG emission for therapeutic proton beams incident on a PMMA phantom were reconstructed. The proposed system achieves reasonable accuracy in range prediction.